The Indonesia Legal Education: Advancing Law Student’s Understanding to Real Legal Issues - Prasanthi, Antarin; ., Daryono (The Indonesian Journal of Socio-Legal Studies, 2023)
Law has been claimed to be insensitive to the real legal issues that led to being unjust and controversial. Those real legal issues most commonly coexisted with the underlying social, cultural, economic, and political issues. In a civil law country, Indonesia, however, the courts often denied those non-legal issues into consideration. Similarly, legislative rules only focus on legal doctrines. They assumed that those non-legal issues were irrelevant to the court's role as the guardian of the rule. This misled understanding is more likely caused by a lack of comprehension of the multifaceted legal problems. One of the causes is the law graduate who is taught to be more a doctrinal-practiced lawyer than a legal scholar. The curriculum of law school in this regard has not adequately equipped law graduates with those real legal issues. There is a need for compulsory courses relevant to the socio-legal understanding to comprehend those non-legal issues that affect legal and normative order. The socio-legal understandings will take great consideration of rapid social changes and progressive rule in a transitional. This is relevant to the current Ministry of Education and Culture policy in 2020 known as the freedom to learn to open up a law curriculum with real legal issues and expand student comprehension of multidisciplinary perspectives on law. This paper examines the necessity to expand the law school curriculum for enabling the comprehension of the rapid social changes affected by the law and the need for progressive legal education reform in the civil law country Indonesia.